ANALYSIS OF CREATIVE THINKING ABILITY IN THE IMPLEMENTATION OF THEMATIC LEARNING IN CLASS V STUDENTS OF SD N 1 PANJER ACADEMIC YEAR 2018/2019 - Peni Setyorini; Nurhasanah Nurhasanah; Kartika Chrysti Suryandari (Universitas Sebelas Maret, 2018)
Thematic learning is divided into themes that combine several subjects of learning. The ability to think creatively should be formed from an early age to meet the golden generation of 2045. The purpose of this study was to analyze the ability to think creatively in the application of thematic learning in class V students of SD Negeri 1 Panjer in 2018/2019 academic year. This study used descriptive qualitative method. The research subjects were the fifth grade students of SD Negeri 1 Panjer namely 19 male students and 8 female students. Data obtained from questionnaires, interviews, and observations. The results of the analysis of the creative thinking abilities of fifth grade students of SD Negeri 1 Panjer are categorized quite good, but it needs improvement in several aspects to achieve the golden generation in 2045. Aspects that need to be improved include aspects of flexible thinking, original thinking, and detailing.